The Importance of Innovation in Creating the Strategic Position of the Company - Erceg, Živko; Kovačević, Biljana; Krunić, Sanja (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
A turbulent environment with never faster and greater changes depicts a situation in which even the strongest often do not find the right solutions and answers. This paper will present an innovative concept, as one of the possible answers to the challenges. Innovation is a process that can and must be managed, because it is innovation that has a direct and huge impact on the achievement leadership positions and business success, but also represents a model and strategy for a new „normality“. Innovation management is the main direction and necessity of modern business. The key role in this is played by the strategic management of a modern organization, because it needs to adequately respond to the challenges in the environment in order to achieve the set goals. The subject of this paper is the contribution of management innovation to the improvement of the innovation process of the organization, which leads to the creation of a better market position, strategic position and competitiveness of the company. The aim of the research is primarily to point out the importance of innovation in achieving a competitive advantage, and to provide the main guidelines to the management of the organization for efficient and effective innovation management. The paper will apply adequate scientific methods for data collection, analysis and processing, such as: analysis method, synthesis method, description method and classification method. It is concluded that only an active innovative approach is the right and lasting solution. If the company is not able to follow the changes and to be innovative, it will inevitably be hit by the crisis.